COVID-19 & Global Food Systems - Swinnen, Johan (2020)
Johan Swinnen CONFERENCE IFIAD Annual Conference 2020 COVID-19 & Sustainable Food Systems - Transforming food systems in times of crises OCT 21, 2020 - 10:00 AM TO 01:00 PM IST